A Ratiometric Fluorescent Biosensor Reveals Dynamic Regulation of Long‐Chain Fatty Acyl‐CoA Esters Metabolism. Issue 25 (11th May 2021) - Wang, Weibo; Wei, Qingpeng; Zhang, Jiayuan; Zhang, Meiqi; Wang, Chuchen; Qu, Renyu; Wang, Yuan; Yang, Guangfu; Wang, Jing
Abstract: Despite increasing awareness of the biological impacts of long‐chain fatty acyl‐CoA esters (LCACoAs), our knowledge about the subcellular distribution and regulatory functions of these acyl‐CoA molecules is limited by a lack of methods for detecting LCACoAs in living cells. Here, we report development of a genetically encoded fluorescent sensor that enables ratiometric quantification of LCACoAs in living cells and subcellular compartments. We demonstrate how this FadR‐cpYFP fusion "LACSer sensor" undergoes LCACoA‐induced conformational changes reflected in easily detectable fluorescence responses, and show proof‐of‐concept for real‐time monitoring of LCACoAs in human cells. Subsequently, we applied LACSer in scientific studies investigating how disruption of ACSL enzymes differentially reduces cytosolic and mitochondrial LCACoA levels, and show how genetic disruption of an acyl‐CoA binding protein (ACBP) alters mitochondrial accumulation of LCACoAs. Abstract : LACSer, a genetically encoded long‐chain acyl‐CoA fluorescence sensor, generates a specific fluorescence response to long‐chain acyl‐CoA, and can be used for the ratiometric quantification of long‐chain acyl‐CoA in cells and subcellular structures. The effects of ACSL and ACBP on the biosynthesis, transport, and downstream metabolism of long‐chain acyl‐CoA can be studied.